ENTREPRENEURIAL ALERTNESS AMONG HIPMI STUDENTS: THE ROLE OF SOCIAL CAPITAL AND PROACTIVE BEHAVIOR - Farid Revaldo; Yuhendri Leo Vrista (Universitas Muhammadiyah Tangerang, 2026)
Entrepreneurship plays an important role in economic growth and job creation, particularly in the context of increasing global competition. However, entrepreneurial alertness among university students remains relatively limited, especially in recognizing and utilizing business opportunities. This study aims to analyze the influence of social capital and proactive behavior on entrepreneurial alertness among HIPMI students at Padang State University. A quantitative causal research design was employed using a census sampling technique involving 90 active members of HIPMI PT UNP. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The findings indicate that social capital and proactive behavior positively and significantly influence entrepreneurial alertness. Social capital enables students to access broader entrepreneurial information, networking opportunities, and business insights, while proactive behavior encourages initiative-taking and responsiveness toward entrepreneurial opportunities. Furthermore, proactive behavior was found to have a stronger influence on entrepreneurial alertness compared to social capital. This study contributes to the entrepreneurship literature by emphasizing the importance of networking and proactive attitudes in strengthening students’ entrepreneurial alertness within entrepreneurship-oriented student organizations.